An underestimated "ghost'' foreign body as an unusual cause of mandibular osseocutaneous fistula formation: Impacted spike of a soccer cleat - Çakmakoğlu, Çağrı; Yeşiloğlu, Nebil; Güvercin, Emre; Akan, İsmail Mithat (Lippincott Williams & Wilkins, 2014)
In this article, the case of a patient with osteocutaneous fistula at the left malar region secondary to impacted spike of a soccer cleat to the mandible is presented. Both the clinical and radiologic diagnoses failed because of an obscure anamnesis of the patient and the unavailability of viewing the spike in orthopantomogram and computed tomography. Surgical extirpation was performed to the 41-year-old man who was injured in a football match 3 months before the presentation and had a swooning history after an accidental booting. There were no early or late complications after the surgery at the end of 9 months. This study shows the importance of both obtaining a definite history of patients and sequential radiologic imaging to make a differential diagnosis between the foreign bodies and cystic or noncystic tumors and inflammatory lesions of the mandible.
WOS: 000335381800137
PubMed ID: 24469364
Keywords: Mandibular Fistula; Soccer Cleat; Sports Injuries; Mandibular Fractures; Football Injuries